2013
DOI: 10.3109/0886022x.2013.828359
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pentoxifylline on gentamicin-induced nephrotoxicity

Abstract: We aimed to investigate the underlying mechanisms responsible for the renoprotective effects of pentoxifylline (PTX) in gentamicin (GEN)-induced nephropathy. On this purpose, 26 female Wistar rats (200-250 g) were included and four groups were formed. The first one was the control group (n:5). The rats in other groups (n:7 for each) received 50 mg/kg twice daily intraperitoneal (i.p.) PTX, 100 mg/kg i.p. GEN and both GEN and PTX at the same doses for consecutive 8 days, respectively. Rats were weighed both at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…In nephrotoxic animal models induced by gentamicin and amikacin, PTX showed antioxidative and renoprotective effects [11,18]. Wang et al [19] and Zhou et al [20] also reported its kidney protective effects by inhibiting the appearance of TNF-α, IL-1β, and NO and inhibiting tubulointerstitial fibrosis in animal models.…”
Section: Introductionmentioning
confidence: 97%
“…In nephrotoxic animal models induced by gentamicin and amikacin, PTX showed antioxidative and renoprotective effects [11,18]. Wang et al [19] and Zhou et al [20] also reported its kidney protective effects by inhibiting the appearance of TNF-α, IL-1β, and NO and inhibiting tubulointerstitial fibrosis in animal models.…”
Section: Introductionmentioning
confidence: 97%
“…The pathogenesis of gentamicin nephrotoxicity involves multiple pathways, including oxidative stress, inflammation, reduced renal blood flow, and increased nitric oxide (NO) level [2, 3]. Several agents have been used, with various degrees of success, to ameliorate or prevent gentamicin nephrotoxicity [46]. …”
Section: Introductionmentioning
confidence: 99%
“…The most common side effect of kanamycin is nephrotoxicity [2][3][4][5][6][7][8][9] and the drug accumulates in the kidneys 10-50 times more than in the plasma. Although it has been reported that kidney damage occurred in 25-50% of patients, pentoxifylline might show a renoprotective effect in some diseases resulting from its vasodilator, antioxidant, and microcirculatory features [9,11,15,22].…”
Section: Discussionmentioning
confidence: 99%
“…Tubular necrosis, epithelial edema of proximal tubules, tubular fibrosis, and perivascular inflammation might also be observed in aminoglycoside-induced nephrotoxicity [9]. Pentoxifylline produces no histopathological changes or an induction of apoptosis in the kidneys [3], while necrosis and apoptosis of tubular epithelial cells, tubular dilatation, increased connective tissue mass in some areas of the interstitium, an enlarged glomerulus or Bowman's capsule, neutrophil or MNC infiltrates, and hemorrhage in some areas of the interstitium have been reported in amikacin-or gentamycin-induced nephrotoxicity [3,12,16,17]. In the current research, pentoxifylline prevented tubular damage induced by kanamycin, but did not inhibit infiltration by MNCs (Table 1, Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation